Implementing technology to support the deteriorating patient in acute care: evaluating staff views. (9th September 2021) - Irons, Ashleigh; McPeake, Joanne; Stuart, John; MacNeilage, Shona; Fisher, Ann-Frances; Cooper, Mark; Johnston, Bridget
Abstract : Background: Early warning scores (EWS) have been widely used to aid in the detection of deterioration. The use of technology, alongside EWS, may improve patient safety and lead to improvements in the accuracy of documentation. Aim: The aim of this service evaluation was to understand nurses' and healthcare support worker views around the implementation of handheld electronic devices for documenting care related to the deteriorating patient. Methods: Before the implementation of an electronic handheld device, in-depth semi-structured interviews with nursing staff and healthcare support workers were undertaken to explore the context for improvement. The Consolidated Framework for Implementation Research was used to analyse, organise and present data, to ensure systematic inquiry across the range of potential facilitators and challenges perceived by staff. In all, 11 interviews were undertaken across three speciality areas (four wards). Findings: Challenges to the use of new technology included staff apprehension around training and education needs and the uncertainty of technological reliability in the clinical setting. Potential facilitators to support the implementation of this technology were: the potential for improved communication across the individual ward and hospital setting and the potential for more streamlined processes for escalation of concerns. Conclusion: Three main recommendations for practice emerged. First, nurses should be involved in the development of the systems. Appropriate time is required to embed the technology in practice. Finally, thought must be given not just to the absolute number of devices required and their reliability, but also how new technology interacts in each individual context.